2021
DOI: 10.1002/ncp.10801
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition screening and diagnosis tools: Implications for practice

Abstract: Despite the prevalence of protein‐calorie malnutrition (PCM) in acute‐care hospitals and long‐term care centers, a national and global consensus on nutrition screening and malnutrition diagnosis is lacking. PCM is associated with various acute and chronic complications, such as impaired wound healing, increased risk for infection, debility, and increased risk for rehospitalization. The consequences of PCM are also incredibly costly to both the patient and the healthcare facility. The purpose of this paper is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…However, nutrition screening is far from ideal. Although the importance is already obvious, the practice of nutrition screening and malnutrition diagnosis is lacking (17). Li et al (18) reported that only 0.5% of patients with cancer received nutrition screening at admission, but the prevalence of malnutrition was up to 44.9% actually in the same cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, nutrition screening is far from ideal. Although the importance is already obvious, the practice of nutrition screening and malnutrition diagnosis is lacking (17). Li et al (18) reported that only 0.5% of patients with cancer received nutrition screening at admission, but the prevalence of malnutrition was up to 44.9% actually in the same cohort.…”
Section: Discussionmentioning
confidence: 99%
“…34 discussion of validated malnutrition screening and diagnosis tools can be found in a review by House and Gwaltney. 35 More recently, literature on nutrition assessment has focused on sarcopenia and its association with perioperative outcomes. Though several clinical definitions for sarcopenia exist, common themes include low muscle mass, low strength, and low physical performance.…”
Section: Perioperative Nutrition Assessmentmentioning
confidence: 99%
“…Still, serum albumin levels are an area of attention for perioperative risk stratification given its association with surgical complications 34 . A detailed discussion of validated malnutrition screening and diagnosis tools can be found in a review by House and Gwaltney 35 …”
Section: Perioperative Nutrition Assessmentmentioning
confidence: 99%
“…Therefore, rapid assessment and improvement in nutritional status play a vital role in the treatment and prognosis of patients with CVD. 10 Prognostic nutritional index (PNI) is a new nutritional immune inflammation index determined by analyzing the complex linear prediction model of serum albumin level, transferrin, delayed hypersensitivity, and triceps skinfold thickness. 11 PNI has been used to evaluate the nutritional status of patients with various diseases and is easy to calculate.…”
Section: Introductionmentioning
confidence: 99%